Update on Edoxaban for the Prevention and Treatment of Thromboembolism: Clinical Applications Based on Current Evidence - Ali Zalpour; Thein Hlaing Oo (Advances in Hematology)
Vitamin K antagonists (VKA) and heparins have been utilized for the prevention and treatment of thromboembolism (arterial and venous) for decades. Targeting and inhibiting specific coagulation factors have led to new discoveries in the pharmacotherapy of thromboembolism management. These targeted anticoagulants are known as direct oral anticoagulants (DOACs). Two pharmacologically distinct classes of targeted agents are dabigatran etexilate (Direct Thrombin Inhibitor (DTI)) and rivaroxaban, apixaban, and edoxaban (direct oral factor Xa inhibitors (OFXaIs)). Emerging evidence from the clinical trials has shown that DOACs are noninferior to VKA or low-molecular-weight heparins in the prevention and treatment of thromboembolism. This review examines the role of edoxaban, a recently approved OFXaI, in the prevention and treatment of thromboembolism based on the available published literature. The management of edoxaban in the perioperative setting, reversibility in bleeding cases, its role in cancer patients, the relevance of drug-drug interactions, patient satisfaction, financial impacts, and patient education will be discussed.